Queens College: A Program for Math Teachers Requires a Complex Formula. (April 2013) - Artzt, Alice F.; Curcio, Frances R.; Sultan, Alan
Teacher educators have not been sitting quietly by the side as others have demanded changes in teacher preparation programs. Across the nation, scores of efforts are underway to recruit, train, induct, and retain a highly skilled class of professionals for American schools. These stories cover just a fraction of the initiatives, projects, and programs launched by school districts, universities, foundations, and others, all aimed at advancing student learning by improving teaching. A program that produces math teachers and a healthy retention rate does so by wrapping itself around students and giving them time to learn and grow into the profession.